The Role Of Environmental Media In Raising Awareness Of Sustainable Development Goals - Djoudi, Cherifa (University of Eloued جامعة الوادي, 2024)
Abstract: There is no doubt that the media plays an indispensable role in raising awareness about any issue and presenting it to the public for the necessary attention. Often, the media only becomes alert and provides coverage when an environmental disaster strikes. However, sometimes this coverage comes too late, after the disaster has already affected human lives. Therefore, it is essential for the media to fulfill its role in educating the public about environmental disasters by developing long-term programs and plans to demonstrate the extent of the damages and severe consequences that disasters can cause to the environment. It is necessary to coordinate efforts between all institutions and entities responsible for the environment with media institutions, which can act as a link with the public.
Keywords: Media; Environmental Media; Environmental Education; Awareness; Sustainable Development